Promoting Quality, Equality and Inclusion through Rethinking Mediums of Instruction in Moroccan Public Schools - ICHOU, Abderazaq; FATHI , Said (International Journal of Language and Literary Studies, 2022)
The multi-linguistic nature of Moroccan society entails the existence of different languages such as Moroccan Arabic, Amazigh Language with its varieties, Standard Arabic, French, and English. From this group, the Moroccan education system opts for two main languages as official mediums of instruction: standard Arabic and French; Arabic starting from the first level in primary school and French beginning from the first year in secondary school. This state of fact challenges the notions of inclusion and equality in the Moroccan education system. Students are being taught in languages different from their mother tongues. The focal objective of this paper is to prove that the gap between the languages used at school and students’ home languages harms the students’ learning outcomes, integration, self-esteem, and self-confidence. To test the validity of this claim, the paper uses a mixed-method approach; a questionnaire is addressed to 200 high school science students to investigate how the absence of their home languages affects their learning outcomes, participation in classroom activities, self-esteem, and self-confidence. In addition, 20 high school teachers are interviewed to detect the negative impact of the mediums of instruction on the students’ learning outcomes, participation in the classroom activities, self-esteem, and self-confidence. Findings reveal that languages of instruction form a real hindrance to guaranteeing quality education for students. All the teachers’ interviewed confirmed that using the official mediums of instruction in the classroom hampers students’ performances and affects their results.